The effect of kegel exercises on urinary incontinence in menopausal women in the Banyuwangi Hindu elderly community - Kusumawati, Diana; Christiana, Indah; Widhi Candra Dewi, Ni Kadek (Jurnal Keperawatan, 2024)
Introduction: Urinary incontinence refers to an individual's inability to restrain or control the discharge of urine due to weakness of the pelvic floor muscles and bladder muscles that are unable to control urine. This causes contamination of skin diseases in the genital area, quality of sleep, and decubitus. Prevention efforts can be provided with non-pharmacological therapy by doing Kegel exercises to stretch the pelvic floor muscles. The mechanism of action strengthens the capacity of the bladder sphincter. Objectives: This study aimed to determine the effect of Kegel exercises on urinary incontinence in postmenopausal women in the Banyuwangi Hindu elderly community in 2023. Methods: This research employed a pre-experimental research design with a one-group pre-test post-test research design of 18 respondents using a purposive sampling technique. Statistical analysis using the Wilcoxon test. Results: The study's results before the intervention were those who experienced urinary incontinence in the elderly with a minimum value of 13, a median value of 17.50, and a maximum value of 22. After the intervention, those experiencing urinary incontinence had a minimum value of 4, a median value of 7.44, and a maximum value of 12.  The findings of this research, analyzed using the Wilcoxon Test with SPSS, yielded a significance value of p = 0.000, which is less than 0.05. This indicates that Kegel Exercise has an impact on Urinary Incontinence in Menopausal Women in the Banyuwangi Hindu Elderly Community in 2023. Conclusions: Kegel exercises contract, increase muscle tone, improve healing by up to 50%, and form a supporting structure for the pelvis, vagina, urethra, and rectum to affect the inability to urinate under control.